2023
DOI: 10.1093/rheumatology/kead104.189
|View full text |Cite
|
Sign up to set email alerts
|

P148 Long-term survival of patients with idiopathic inflammatory myopathies: Anatomy of a single-center cohort

Abstract: Background/Aims Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of immune-mediated systemic diseases, characterized by muscle inflammation and multiple systemic manifestations. We aimed to characterize clinical manifestations, course, treatment, and mortality of IIM patients. We have also attempted to assess predictors of mortality in IIM. Methods Retrospective single center study IIM patients followed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In light of the newer outcome measure tools and the development of myositis‐specific and myositis‐associated antibodies, the data on the prognosis of IIM is evolving. Numerous worldwide studies have reported the prognostic factors for the outcome and survival of patients with IIM 1–7 . However, the validated outcome measures were used only in a few cohort studies 2,5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the newer outcome measure tools and the development of myositis‐specific and myositis‐associated antibodies, the data on the prognosis of IIM is evolving. Numerous worldwide studies have reported the prognostic factors for the outcome and survival of patients with IIM 1–7 . However, the validated outcome measures were used only in a few cohort studies 2,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of these patients has varied from 54%, as reported in the Tennessee study 8 to 90% as available from European studies 3,9 . The common predictors of mortality reported were age at onset, cardiac involvement, presence of interstitial lung disease (ILD) and malignancy 4,5,7,10 …”
Section: Introductionmentioning
confidence: 99%